Santità ed evangelizzazione della società - Semeraro, Marcello Card (Alpha omega, 2022)
Holiness is not the fruit of human effort, but a gift of God. It is above all the experience of being loved by God, of freely receiving his love, his mercy. It is this experience that impels us to witness, and therefore to evangelization, more with the attitude of life than with words. The true saint is always a living gospel. The Second Vatican Council wished to free the baptized from the elitism of holiness: All the faithful of whatever state or degree are called to the fullness of Christian life and to the perfection of charity (cfr. Lumen Gentium, 40). Canonized holiness gives visibility to the pearls of this widespread holiness which, like leaven, ferments the “dough” of society. Moreover, recently Pope Francis has opened up the possibility of beatification of those Christians who, following Christ, voluntarily and freely offered their lives for others and persevered until death in this commitment.